1986
DOI: 10.1111/j.1476-5381.1986.tb09498.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological analysis of the inhibition by pirenzepine and atropine of vagal‐stimulated acid secretion in the isolated stomach of the mouse

Abstract: 1 The muscarinic receptors involved in the vagal stimulation of gastric acid secretion in the mouse isolated stomach assay have been examined by analysing the effects of pirenzepine and atropine on fully-defined frequency-effect curves. 2 Both atropine and pirenzepine produced concentration-dependent inhibition of vagal-stimulated acid secretion in a manner consistent with a model describing competitive antagonism of endogenous acetylcholine, which was assumed to be released by vagal stimulation. 3 The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

1987
1987
1995
1995

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…Functionally, pirenzepine was 100-fold and telenzepine 8-fold less potent than atropine as an inhibitor of carbachol-stimulated AP accumulation. These data are consistent with other studies showing 5-to 25-fold greater potency of telenzepine compared with pirenzepine [14,15] and 5-to 10-fold greater potency of atropine compared with telenzepine [14], These findings of a low to intermediate affinity of pirenzepine and telenzepine for parietal cell receptors are consistent with the binding [16] and func tional studies [14,[17][18][19] of others, indicat ing clearly that parietal cells do not possess a muscarinic receptor of an Ml-subtype.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Functionally, pirenzepine was 100-fold and telenzepine 8-fold less potent than atropine as an inhibitor of carbachol-stimulated AP accumulation. These data are consistent with other studies showing 5-to 25-fold greater potency of telenzepine compared with pirenzepine [14,15] and 5-to 10-fold greater potency of atropine compared with telenzepine [14], These findings of a low to intermediate affinity of pirenzepine and telenzepine for parietal cell receptors are consistent with the binding [16] and func tional studies [14,[17][18][19] of others, indicat ing clearly that parietal cells do not possess a muscarinic receptor of an Ml-subtype.…”
supporting
confidence: 82%
“…The receptors on isolated parietal, chief and somatostatin cells are less sensitive to pirenzepine or telenzepine than to atro pine, suggesting that canine gastric mucosal cells do not possess a definitive M 1 receptor. Further investigation is needed to clarify whether a gastric Ml receptor exists, for example on intramural neurons, or whether the apparent affinity of muscarinic antago nists in vivo reflects interaction of effects between muscarinic receptors on several cell types or mechanisms such as altered delivery to the receptor site [19]. The presence of muscannic receptors with a specificity dis tinct from either M l-or M2-subtypes may represent a third muscarinic subtype of pharmacological interest.…”
mentioning
confidence: 99%
“…Acid secretory responses were expressed as ApH, that is the difference between basal pH, measured immediately prior to experimental intervention, and stimulated pH. The stomach preparations were electrically stimulated with a pair of platinum, ring electrodes (ring diameter 2 mm, wire diameter 0.5 mm) placed either side of the stomach in the region of the fundic glands (Black & Shankley, 1986). The intensity of stimulation was standardized at 10 V with square wave pulses of 0.5 ms duration.…”
Section: Introduction Methodsmentioning
confidence: 99%
“…Black and Shankley (16) reported that the field stimulation under physostigmine treatment could evoke stable acid secretion in mice by cumulatively increasing frequency (the cumulative method). In their experimental condition without physostigmine, however, unstable responses with an initial peak were often observed during continuous stimulation (8).…”
Section: Discussionmentioning
confidence: 99%